Fibrocystic Breast Tumor: A Case Report - Ferry Kalitouw; Christian Manginstar; Melfrits Siwabessy (Universitas Sam Ratulangi, 2023)
Abstract: Fibrocystic breast tumor is the most common benign type of breast diseases that affects millions of women worldwide. Fibrocystic breast changes are classified as non-proliferative, proliferative without atypia, or proliferative with atypia. We reported a 34-year-old woman presented with a right breast evaluation of breast tumors since one year before admission. On examination, a solid and hard breast tumor measuring 15x10 cm was palpable, well-defined, tender, mobile, and no nipple discharge. The patient underwent two times of core biopsy and the results were fibrocystic changes. Although clinically the breast tumor had a malignant appearance, but the results of core biopsy examinations revealed fibrocystic changes. The patient was managed by wide excision of the evaluated breast tumor with preservation of the breast skin and nipple areolar complex to maintain its function and aesthetic. In conclusion, evaluation of breast tumors must go through a triple diagnostic procedure namely clinical, imaging, and histopathological examinations. Fibrocystic breast tumor can be managed with wide excision of the tumor with preservation of the skin structure and nipple areolar complex of the breast to achieve a natural aesthetic. Keywords: fibrocystic breast tumor; wide excision of tumor; evaluation of breast tumors